Comparison of Soil-Freezing and Soil-Water Characteristic Curves of Two Canadian Soils - Junping Ren; Sai K. Vanapalli (Vadose Zone Journal, 2019)
The drying–wetting and freezing–thawing cycles significantly influence the soil pore water in the vadose zone in permafrost and seasonally frozen regions. The soil-freezing characteristic curve (SFCC) describes the relationship between unfrozen water content and subzero temperature in a soil at frozen condition. Several studies suggest that the SFCC of a frozen saturated soil is similar to soil-water characteristic curve (SWCC), which describes the relationship between water content and suction for a soil under unfrozen unsaturated condition. In the present study, the similarity between SFCC and SWCC, and possible reasons for the hysteresis of SFCC are succinctly reviewed. The SFCC and SWCC of two Canadian soils were measured and critically interpreted to understand the fundamental behavior of SFCC in comparison with the SWCC. The observed hysteresis of SFCC for the two soils was mainly associated with the supercooling of pore water. The measured SFCC and SWCC of the two soils show quantitative dissimilarity rather than similarity. This may be attributed to the experimental limitations and possible fundamental differences between drying–wetting and freezing–thawing processes. In addition, several concerns regarding the similarity between SFCC and SWCC are discussed. The present study highlights that rigorous investigations are required for better understanding the SFCC to facilitate its use for cold-region engineering practice applications.